Identifikasi dan Kajian Pemanfaatan Sumber Air Sebagai Sumber Air Baku di Kawasan Fungsi Lindung Taman Nasional Gunung Palung Kabupaten Kayong Utara - Riduansyah, Riduansyah; Widiarso, Bambang (Pedontropika: Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2023)
The sustainability of water resources needs to be maintained considering its very important benefits in life and development. Water can be used as raw water for drinking water, water for irrigation, water for daily needs such as bathing and washing, water for industrial needs or water used for other purposes such as fishing and swimming pools. The aim of this study is to provide an accurate and comprehensive condition of the location of potential raw water sources that can be used as raw water sources, identify and study raw water sources in protected functional areas, and provide recommendations for potential raw water sources based on results of the studies carried out. The methods used to identify raw water sources are field observations, interviews, and focus group discussions (FGD). The results of the study show that the locations of water sources that fall into the class I water quality category are water sources located within the Sukadana District area, including: Riam Berasap, Lubuk Tapah/Mentubang, Tiang Jurung, Batu Gamal, Ceremai, Lubuk Baji, Air Genteng /Air Genderia/Peramas, Ne' Utong, Air Unjun/Semebruang, Air Padan/Air Berguruh, Air Keladi, Air Panjang/Sembutak, Air Berguruh/Senebing, Tambak Rawang, Kemambak, Lubuk Tapah/Begasing, Air Mask, Air Pematang/ Pangkalan Taib, Simpang Gasi/Gasi Anang, Pangkalan Ja'I, Air Manggis, and Simpang Saut.